Perancangan Teknologi Augmented Reality Pengenalan Produk Skincare - Pastima Simanjuntak; Sri Zetli (LPPM Universitas Putera Batam, 2025)
Skincare products have an important role in facial care because they contain active ingredients that function to overcome various skin problems such as acne, black spots, blackheads, and excess oil. However, in Batam City, the number of skincare products that enter without verification of eligibility raises trade and consumer trust issues. Consumers need tools to understand and choose the right products. The purpose of the research is to design and develop an Augmented Reality (AR) based application to introduce skincare products in Batam City through Android devices, in order to facilitate consumers in visualizing and obtaining information about products in a more interactive and real way. The methodology used in this research involves application development using the Unity platform and Vuforia Engine with the target Android platform. The technology applied is marker-based Augmented Reality, where the implementation process includes 3D modeling of skincare products, integrating product-related information such as functions, how to use, and side effects, and using markers-such as those found in brochures or product catalogs-as a trigger for displaying objects and information in the form of Augmented Reality visuals. The result of the research is an AR application that successfully displays 3D objects of skincare products accompanied by descriptive information. This application runs on Android devices and provides a more real product visualization experience and supports consumer understanding of skincare products.